European Union development assistance to Asia (Destined to Cooperate? Various Dimensions of European Union Policy Towards Asian Countries, 2024)
The European Union is the largest provider of official development assistance (ODA). By leveraging this position, the EU aims to promote globally significant values and political goals such as conflict prevention, democracy, rule of law, and respect for human rights. The aim of this chapter is to present EU cooperation for development, with a particular focus on development assistance for Asia. By outlining the characteristics of EU development policy and its financial resources, it addresses questions regarding the legal basis of EU ODA and its principles, as well as the major aid donors within the EU, the countries receiving the largest amounts of aid, and thematic priorities. This chapter also serves as an introduction to the first part of the book, which presents analyses of EU development assistance to three very different Asian countries.